A representação do negro e da negra em Olhos d'água: sujeitos de dor, luta e esperança - Túlio Romualdo Magalhães (2023)
Evaristo's work has increasingly drawn the attention of literary critics and the reading public. In the first case, the growing number of dissertations, theses, and other academic works dedicated to analyzing Evaristo's short stories, novels, and poetry stands out. In this sense, this study investigates how the black subject is represented in the short stories from the anthology Olhos d’água (EVARISTO, 2016) by the Brazilian writer Conceição Evaristo. For that, studies on the contemporary black feminist debate, the discussion around Afro-Brazilian literature, and the concepts of memory and identity worked as reading keys that helped in the analysis of the corpus. Furthermore, a critical reading of short stories from Olhos d'água was promoted. Finally, it was found that Evaristo, from a powerful and profound language, makes use of a wide repertoire to represent the black subject through pain, struggle, and hope.